The ‘Volksreformation’ of Thomas Müntzer in Allstedt and Mühlhausen - Scott, Tom (The journal of ecclesiastical history, 1983)
As the fieriest champion of the Radical Reformation Thomas Müntzer remains an enigma. A spate of recent works has greatly increased our knowledge of the development of his theology and of his contribution to the Peasants' War in central Germany, but they have failed to resolve the precise relationship between his theological convictions and his involvement in social revolution. A profusion of Marxist writings, above all from East Germany, has stressed the objective function of his religious radicalism in promoting and legitimating mass rebellion in Saxony and Thuringia at the expense of its subjective intention, whilst the bulk of Western scholarship, in particular Walter Elliger's massive though scarcely definitive biography, has emphasised the primacy of his theological vision, to which social and political concerns were at best subordinate or tangential.